Procedurally fair co-determination with endogeneous value uncertainty: An experiment - Werner Güth; Ludivine Martin; Tibor Neugebauer; Sotiria Xanalatou (Games, 2025)
We present an experimental test of a procedurally fair co-determination mechanism where group members reduce their value uncertainty before submitting bids for a joint project. The results suggest a relatively efficient mechanism, with unprofitable projects being largely rejected and profitable ones accepted. Repeated interactions tended to enhance the efficiency, while uncertain information reduced it. The subjects invested surprisingly little search effort to reduce the uncertainty about the costs and benefits, and appeared to trade off search costs against higher bids.
Keywords: C92; D70; D81; J52; L20; 330; corporate governance; joint venture; experiment; auction; uncertainty